PHYTOPLANKTON OF CASPIAN - Aysha Sharapatinovna Gasanova; Galina Vitalevna Kovaleva; Kais Magomedovich Guseynov; Magomedzagid Kaisovich Guseynov (Юг России: экология, развитие, 2015)
Aim. The composition of the species of the phytoplankton in the Russian sector of the Caspian Sea in conditions of transgression, anthropogenic and chemical contamination has been studied.Location.The Russian sector of the Caspian SeaMethods. The phytoplankton samples were collected at the depths of 8 – 50m by the use of the Nansen bathometer and subsequently were fixed in 4% formalin. The office processing was carried out in a box of Nozhotta type, which has the volume of 0.1 ml and the triplicate surface, under the light microscope of Biolam P15. The system of domestic diamotologists was used during the classification of Bacillariaphyta, as for the classification of Dinophyta, the Dodge scheme was applied. Cyanophyta algae were classified according to the system of A.A. Elenkina with the amendments adopted by A.I. Proshkin-Lavrenko and V.V. Makarova. The classification of the Chlorophyta division has been done according to the Smith system.Results, main conclusions. Presented the taxonomic structure and the lists of species of the phytoplankton community in the sea coastal shallow waters Russian sector of the Caspian Sea have been presented. A high floristic diversity and domination of small cell forms are characteristics of the modern structure of the coastal shoal waters of the Dagestan part of the Caspian Sea. The auttaclimatizant of 1934, Pseudosolenia calcaravis, has not been discovered in the plankton of the researched water area. The phytoplankton community has been represented by 58 species of six groups: Cyanophyta, Bacillariaphyta, Dinophyta, Euglenophyta, Chlorophyta and the small flagellate. Bacillariaphyta were the basis of both the taxonomic diversity and the biomass. Cyanophita prevailed in number.